Comparison of Hypnotic Suggestion and Transcranial Direct-Current Stimulation Effects on Pain Perception and the Descending Pain Modulating System: A Crossover Randomized Clinical Trial - Gerardo Beltran Serrano; Gerardo Beltran Serrano; Gerardo Beltran Serrano; Gerardo Beltran Serrano; Laura Pooch Rodrigues; Bruno Schein; Andressa Souza; Iraci L. S. Torres; Luciana da Conceição Antunes; Felipe Fregni; Felipe Fregni; Wolnei Caumo; et al. (Frontiers in Neuroscience, 2019)
Objectives: This paper aims to determine if hypnotic analgesia suggestion and transcranial direct-current stimulation (tDCS) have a differential effect on pain perception. We hypothesized that transcranial direct-current stimulation would be more effective than hypnotic analgesia suggestion at changing the descending pain modulating system, whereas the hypnotic suggestion would have a greater effect in quantitative sensory testing.Design: This is a randomized, double blind and crossover trial.Settings: All stages of this clinical trial were performed at the Laboratory of Pain and Neuromodulation of the Hospital de Clínicas de Porto Alegre.Subjects: Were included 24 healthy females aged from 18 to 45 years old, with a high susceptibility to hypnosis, according to the Waterloo-Stanford Group Scale of Hypnotic Susceptibility, Form C (15).Methods: The subjects received a random and crossover transcranial direct-current stimulation over the dorsolateral prefrontal cortex (2 mA for 20 min) and hypnotic analgesia (20 min).Results: Only hypnotic suggestion produced changes that are statistically significant from pre- to post-intervention in the following outcomes measures: heat pain threshold, heat pain tolerance, cold pressure test, and serum brain-derivate-neurotrophic-factor. The analysis showed a significant main effect for treatment (F = 4.32; P = 0.04) when we compared the delta-(Δ) of conditioned pain modulation task between the transcranial direct-current stimulation and hypnotic suggestion groups. Also, the change in the brain-derivate-neurotrophic-factor was positively correlated with the conditioned pain modulation task.Conclusion: The results confirm a differential effect between hypnotic suggestion and transcranial direct-current stimulation on the pain measures. They suggest that the impact of the interventions has differential neural mechanisms, since the hypnotic suggestion improved pain perception, whereas the transcranial direct-current stimulation increased inhibition of the descending pain modulating system.Clinical Trial Registration:www.ClinicalTrials.gov, identifier NCT03744897.Perspective: These findings highlight the effect of hypnotic suggestion on contra-regulating mechanisms involved in pain perception, while the transcranial direct-current stimulation increased inhibition of the descending pain modulating system. They could help clinicians comprehend the mechanisms involved in hypnotic analgesia and transcranial direct-current stimulation and thus may contribute to pain and disability management.